Non-Coding RNAs Regulating Morphine Function: With Emphasis on the In vivo and In vitro Functions of miR-190 - Zheng, Hui; Law, Ping-Yee; Loh, Horace H. (Frontiers in Genetics, 2012)
Non-coding RNAs, especially micro-RNAs (miRNAs) have been reported to be involved in a variety of biological processes, including several related to the addictive drugs. The biological functions of opioids, one typical type of addictive drugs, have also been suggested to be regulated by non-coding RNAs including miRNAs. In the current review, we will examine a variety of mechanisms in which miRNAs could regulate μ-opioid receptor (OPRM1) activities. By using miR-190 as an example, we will demonstrate the critical roles played by miRNAs at the signal cascade from receptor to the systematic responses, including the possible modulations on the adult neurogenesis and in vivo contextual memory. By using miR-23b as an example, we will also examine the direct effects and mechanisms of miRNAs-mediated regulations of opioid receptor levels and how receptor signaling affects the miRNAs’ expression. Finally we will attempt to provide an discussion on the relationship and interaction between various non-coding RNAs and opioids’ functions.